Improving Students Achievement on Social Science by Using Cooperative Learning Method - Budiatman, Ino; Patriasurya, Ary (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Various attempts have been taken by teachers in improving students achievement in learning social science. One of them is using various methods and strategies to attract students interest to learn the subjects. One of methods that is popular nowadays for elementary school is cooperative learning method. As a method, there are some strategies to deliver the learning materials and three of them are Jigsaw (JIG), Numbered Head Together (NHT), and Make a Match (MaM). This research tries to find out which strategies that is most effective in improving students achievement. The research is conducted in level 5 elementary schools in Tangerang district of Banten Province. The sampel is three schools in choosen by using cluster random sampling. Each of sample is taught same material by using different strategies for four times. Data analysis shows that there is a significant different on students achievement before and after treatment. Further analysis shows that there is no any significant different on students achievements using JIG, NHT, and MaM. The research concludes that all strategies can be used to increase students achievements